2016
DOI: 10.3851/imp3118
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Potential and Mode of Action of Indigofera Heterantha against HSV-2 by Targeting the Early Stages of Infection

Abstract: The extract targets the early and late stages of HSV-2 viral life cycle and thus shows great promise as both a prophylactic as well as therapeutic phytopharmaceutical against HSV-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The use of phytoderivatives is generally transmitted as a consequence of their ancient applications, most of them lately rediscovered, or under stronger evaluation. Scientists have published some experimental data related with isolated vegetal derivatives, for example on specific infections of urogenital pathogens, as Candida vaginal infections [21], some viruses [22], and parasites as Trichomonas [23] or bacteria [24]. In addition, they are widely recommended and included in the design of vegetal-derived formulas for postmenopausal women or for reproductive disorders [25].…”
Section: Discussionmentioning
confidence: 99%
“…The use of phytoderivatives is generally transmitted as a consequence of their ancient applications, most of them lately rediscovered, or under stronger evaluation. Scientists have published some experimental data related with isolated vegetal derivatives, for example on specific infections of urogenital pathogens, as Candida vaginal infections [21], some viruses [22], and parasites as Trichomonas [23] or bacteria [24]. In addition, they are widely recommended and included in the design of vegetal-derived formulas for postmenopausal women or for reproductive disorders [25].…”
Section: Discussionmentioning
confidence: 99%
“…Within this time frame, there were two (1.46%) studies in 2015 [ 6 , 7 ], 15 (10.95%) studies in 2016 [ 1 , 3 , 8 - 20 ], 19 (13.87%) studies in 2017 [ 21 - 39 ], 27 (19.71%) studies in 2018 [ 40 - 64 ], 23 (16.79%) studies in 2019 [ 2 , 65 - 86 ], 24 (17.52%) studies in 2020 [ 87 - 110 ], and 27 (19.70%) studies in 2021 [ 111 - 137 ]. Regarding the type of studies reviewed, 121 (88.32%) studies included in vitro elements [ 2 , 3 , 6 - 12 , 14 - 20 , 23 - 26 , 28 - 42 , 44 - 47 , 49 - 56 , 58 - 64 , 66 , 68 - 72 , 74 - 77 , 79 , 80 , 82 - 87 , 89 - 118 , 120 , 122 - 133 , 135 - 139 ] and 23 (16.79%) in vivo [ 2 , 13 , 15 , 18 , 22 , 25 , 27 , 28 , 37 , 43 , 48 , 56 , 62 , 67 , 73 , 78 , 81 , 100 , …”
Section: Reviewmentioning
confidence: 99%
“…When determining the effectiveness of the proposed interventions, five (3.65%) were shown not to be effective [84,107,126,131,139], three (2.19%) were somewhat effective [21,46,53], and 128 (93.43%) were effective as potential managements for resistant strains of HSV [1][2][3][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][47][48][49][50][51][52][54][55][56][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]…”
Section: Data Extractionmentioning
confidence: 99%
“…A subsequent study by the authors showed the extract elicits its effect early in the viral replication cycle by blocking HSV-2 attachment, adsorption, and entry into host cells. 191 Furthermore, He et al 39 observed an ethanolic extract of the fungus Antrodia camphorata to have antiviral activity against HSV-1 (strain F) and HSV-2 (strain G). Although not nearly as potent as acyclovir, A. camphorata was found to inhibit viral plaque formation with IC 50 values of 61.2 mg/ml and 57.5 mg/ml for HSV-1 and HSV-2, respectively.…”
Section: Asiamentioning
confidence: 99%
“…A subsequent study by the authors showed the extract elicits its effect early in the viral replication cycle by blocking HSV-2 attachment, adsorption, and entry into host cells. 191…”
Section: Single Herbs In Vitromentioning
confidence: 99%